Standaard verpleegvoorskrifte vir voorgeboorte kliënte - S. Venter; P. du Plooy (AOSIS, 1984)
Inspired after attending the course in scientific education for the nursing process, given by Mrs I.M. Miles at the J.G. Strijdom Hospital in February 1984, this standard nursing care plan for antenatal clients was born. It is based on the nursing module.